Governance and cultural organisations in Portugal. An approach to a typological interpretation. - Mendes, Tiago; Vargas, Carlos (79th Annual Midwest Political Science Association Conference, 2022)
We argue that the Portuguese government is promoting a ‘governance turn’ in the prosecution of its national cultural policy, testing alternative and innovative models, through different frameworks and achieving different results in each case. This change goes beyond a mere trend of managerial autonomisation of public agencies, encompassing governance practices such as the inclusion of both public (central and local), private and third sector agents in the institutional arrangements, the search for self-sustainable financing models, and the option for more adequate organizational frameworks that contribute to the implementation of national cultural policies. Our argument is emphasized through the consideration of three case studies – public or public-private cultural foundations located in the northern region of the country – that were created between 1994 and 2011, substantially funded by the government but building bridges with other founders. This research paper aims at analysing its organizational configurations and the legislative modifications that occurred during our timeframe period, in response to particular institutional needs and a changing political context. We identify key typological features of governance organizational arrangements and analyse their role and impact in Portuguese cultural policies.